The Effect of Electrode Angle on the Backward Directional Longitudinal Against Penetration Percentage - Hafni Hafni; Rifqi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
Shielded Metal Arc Welding (SMAW) is one of the liquid welding processes (fusion welding) that produces a homogeneous fusion of the electrode with the base metal (base metal), which is caused by an electric arc that generates high heat to melt the electrode and base metal (base metal). simultaneously and protected by a shielding gas from the chemical reaction of the electrode flux. The depth of fusion formed is determined by the heat input, the electrode angle and the welding direction. The research was conducted at the Mechanical Engineering Laboratory of the Padang Institute of Technology. The base metal used is low carbon steel ST 37 with a thickness of 10 mm and a length of 100 mm. width 100 mm. Welding is carried out on the surface of the base metal in the flat position, the type of connection (weld type) is a surfacing weld with 4 welding lines, each strip having a distance of 20 mm. Weld length 100 mm. AWS E6013 electrode specifications with a diameter of 3.2 mm. SMAW welding machine AC current with a voltage of 30 V. current 85 A. The measured electrode angle between the electrode and the welding line is 75o, 85o, 90o. The backward welding direction where the electrode draws the welding fluid into the welding path and the normal arc height where the distance between the electrode and the base metal is equal to the diameter of the electrode. From the welding results, a penetration presentation will be obtained, namely the ratio of the depth of fusion to the width. The research results obtained welding speed: 2.48 mm/s for electrode angle 75o, 2.49 mm/s for electrode angle 85o and 2.51 mm/s for electrode angle 90o. Heat input for electrode angle 750 is 1015.93 J/ mm , the heat input for the electrode angle 85o is 1024.20 J/mm and the heat input for the electrode angle 90o is 1015.93 J/mm. From the comparison of the width with the depth of fusion, it is obtained; The electrode angle 85o has a penetration presentation of 9.85%, which is better in height than the electrode angle 75o, which has a penetration presentation of 8.43%, and the electrode angle 90o has a penetration presentation of 8.35%..